2001
DOI: 10.1023/a:1010992900387
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Accumulation of lipid metabolites, such as palmitoylcarnitine and lysophosphatidylcholine, is thought to be a major contributor to the development of cardiac arrhythmias during myocardial ischemia. This arrhythmogenicity is likely due to the effects of these metabolites on various ion channels. Diabetic hearts have been shown to accumulate much higher concentrations of these lipid metabolites during ischemia, which may be an important factor in the enhanced incidence of arrhythmias in diabetic hearts. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Currently, the data presented above are in opposition to earlier results of others. Previous reports have demonstrated that PC may strongly activate [ 3 , 4 ] and inhibit [ 4 , 5 ] L-type Ca 2+ current (Ica 2+ ). The experiments performed on LCC, incorporated in the lipid bilayer, revealed strong dose-dependent and time-dependent effects of PC on open probability of the channels, with maximal effect achieved at 1 µM PC and within the first minutes of the recording [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the data presented above are in opposition to earlier results of others. Previous reports have demonstrated that PC may strongly activate [ 3 , 4 ] and inhibit [ 4 , 5 ] L-type Ca 2+ current (Ica 2+ ). The experiments performed on LCC, incorporated in the lipid bilayer, revealed strong dose-dependent and time-dependent effects of PC on open probability of the channels, with maximal effect achieved at 1 µM PC and within the first minutes of the recording [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…The experiments performed on LCC, incorporated in the lipid bilayer, revealed strong dose-dependent and time-dependent effects of PC on open probability of the channels, with maximal effect achieved at 1 µM PC and within the first minutes of the recording [ 4 ]. Although, according to the results of the experiments on isolated CM, 10 µM PC exerted immediate inhibition of Ica 2+ [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, fatty acids are a major source of energy for the heart 30 . A shift in substrate preference occurs in diseases that increase the risk of SCA, including cardiac hypertrophy 31 and uncontrolled diabetes 32 ; and accumulation of intermediates of fatty acid oxidation influence arrhythmogenesis in isolated cardiac tissues and cardiac myocytes 33, 34 . For these reasons, we examined genes that may be involved in the uptake and transport of fatty acids in the heart, fatty acid beta-oxidation in mitochondria and the control of beta-oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…L-type Ca 2+ channels (LTCCs) facilitate Ca 2+ influx during late myocyte depolarization, provoking the Ca 2+ -induced Ca 2+ release that sustains the action potential plateau and catalyzes myofilament interaction ( Bodi et al, 2005 ). LCAC superfusion has been found to dose- (1–25 μM) and time- (2–10 min) dependently reduce current density, as well as activation and inactivation kinetics of LTCCs ( Wu and Corr, 1992 ; Liu and Rosenberg, 1996 ; Ziolo et al, 2001 ). This inhibitory effect occurs regardless of intra- or extracellular LCAC delivery, is completely reversible following wash-out, and is consistent across species and preparations ( Wu and Corr, 1992 ; Liu and Rosenberg, 1996 ; Ziolo et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%